Neuropsychological assessment of adults with ADHD: A Delphi consensus study. Issue 4 (4th July 2019) - Fuermaier, Anselm B. M.; Fricke, Jan A.; de Vries, Stefanie M.; Tucha, Lara; Tucha, Oliver
ABSTRACT: Within the clinical evaluation of adults with attention deficit hyperactivity disorder (ADHD), cognitive functions are often assessed to characterize individual cognitive problems and guide treatment planning. However, the composition of an adequate neuropsychological assessment battery remains difficult given the large number of cognitive functions that can be distinguished, the variety of available tools to assess these functions, as well as the cognitive heterogeneity that has been observed between individuals with ADHD. Twenty-seven clinicians and researchers experienced in working with adults with ADHD took part in the present study. This study employed the Delphi methodology in order to compose an assessment battery for the measurement of the most important neuropsychological functions by employing the most suitable measures to assess these functions. Consensus between experts was achieved on a ranking of 16 neuropsychological functions that are important for the neuropsychological assessment of adults with ADHD. Furthermore, measures were suggested to assess each of the neuropsychological functions. The assessment battery as composed in the present study may support research and clinical practice in the selection of appropriate functions and measures for the determination of the individual level of cognitive functioning and treatment planning of adults with ADHD.